LightningBR: Ferramenta Web para Visualização e Análise de Ocorrência de Raios no Brasil - Alves, Elton R.; V. Júnior, Warley M.; Moraes, Alife S. de; Alvino, Diogo da S.; Balieiro, Andson M. (Anais Estendidos do Simpósio Brasileiro de Sistemas Multimídia e Web (WebMedia), 2024)
Monitoring lightning occurrences is extremely important due to the potential negative impacts this phenomenon can cause to human and animal life, civil aviation, and electrical power and telecommunication systems. In this regard, this work presents the LightningBR a web tool developed for analysis and visualization of cloud-to-ground and intra-cloud lightning occurrences, using raw data from the ENTLN (Earth Networks Total Lightning Network). The development of this work consisted of two main parts: the first part involved the creation of the Back-end using a Node.js server, MongoDB Atlas database, and Leaflet JS API. The second part involved the development of the Front-end responsible for the visual aspects of the system. In this stage, HTML (HyperText Markup Language), CSS (Cascading Style Sheets), JavaScript, and Figma were used. The tool’s functionalities were tested with lightning data from an anonymous city in Brazil, proving to be feasible for continuous monitoring of lightning occurrences.